Development of novel fluorescent histamine H₁-receptor antagonists to study ligand-binding kinetics in living cells - Stoddart, Leigh A.; Vernall, Andrea J.; Bouzo-Lorenzo, Monica; Bosma, Reggie; Kooistra, Albert J.; de Graaf, Chris; Vischer, Henry F.; Leurs, Rob; Briddon, Stephen J.; Kellam, Barrie; Hill, Stephen J. (Nature Publishing Group, 2018)
The histamine H1-receptor (H1R) is an important mediator of allergy and inflammation. H1R antagonists have particular clinical utility in allergic rhinitis and urticaria. Here we have developed six novel fluorescent probes for this receptor that are very effective for high resolution confocal imaging, alongside bioluminescence resonance energy transfer approaches to monitor H1R ligand binding kinetics in living cells. The latter technology exploits the opportunities provided by the recently described bright bioluminescent protein NanoLuc when it is fused to the N-terminus of a receptor. Two different pharmacophores (mepyramine or the fragment VUF13816) were used to generate fluorescent H1R antagonists conjugated via peptide linkers to the fluorophore BODIPY630/650. Kinetic properties of the probes showed wide variation, with the VUF13816 analogues having much longer H1R residence times relative to their mepyramine-based counterparts. The kinetics of these fluorescent ligands could also be monitored in membrane preparations providing new opportunities for future drug discovery applications.